Automate humans or humanize automation? The “Atque” Design and Communication System to redefine the relationship between knowledge and know-how - Marta Guarducci; Luca Toschi; Viola Davini; Marco Sbardella; Pandolfini Eugenio (Türkiye İletişim Araştırmaları Dergisi)
This paper introduces the research conducted by the “scientia Atque usus” Research Center for Generative Communication ETS (from now on: sAu Research Center) dealing with the relationship between new technologies and the enhancement of human creativity. sAu Research Center has been working on the impact of automation in social and creative processes and the research group has conceived and developed the “Atque” Design and Communication System: A suite of functional tools for carrying out activities of research, analysis, design, development, documentation, monitoring, communication and training. It is a system which is constantly transforming itself: it is based on the people who are using it and on the projects that have to be realized, so it changes as a living system. It is for this reason that the main characteristic is to be human-centered-design, it enhances human creativity and it fosters the collaboration among people who cooperate in a common project.